A study to find out levels of leisure boredom Present in individuals with history of substance abuse. - Dr.S KAVITHA; DUROJAIYE OLUSHOLA SAMSON (International Journal of Pharma and Bio Sciences, 2017)
Restricted Leisure activities are likely to cause feelings of boredom. Individuals who experience high level of leisure boredom may engage in deviant activities such as substance abuse The aim of this cross sectional study was to estimate the associations between leisure boredom and its relationship with substance abuse. Based on a cross-sectional design study, one hundred patients on admission for de-addiction were recruited from Wisdom De-addiction center Saidapet, and Sumana Goodwill home Guduvanchery, kancheepuram district, participated in this study. All of these patients are between the age ranges of 17-60 years. Alcohol Use Disorder Identification Test and Leisure Boredom questionnaire was administered to the participants. SPSS Version 19.0 was used to analyse data gathered. Findings revealed that highest percentage (44.8%) of patients with history of substance abuse belongs to the age bracket of (26-40) years while the lowest percentage (7.3%) of patients with history of substance abuse comes from the age bracket (>56) years. Further, emerging from this study indicate that there is no significant difference Irrespective of the age, marital status and employment status the boredom levels and alcohol use remains the same. The boredom levels and alcohol use score shows statistical difference among the educated sample. Understanding the individuals with history of substance abuse should be the important focus. Hence, rehabilitation in substance abuse is to encourage abstinence, and then the alcoholic patient must be instructed and guided to organize his time and build up habits of work and leisure which are free of alcohol.